2019
DOI: 10.1371/journal.pone.0225256
|View full text |Cite
|
Sign up to set email alerts
|

The Mastery Rubric for Bioinformatics: A tool to support design and evaluation of career-spanning education and training

Abstract: As the life sciences have become more data intensive, the pressure to incorporate the requisite training into life-science education and training programs has increased. To facilitate curriculum development, various sets of (bio)informatics competencies have been articulated; however, these have proved difficult to implement in practice. Addressing this issue, we have created a curriculum-design and -evaluation tool to support the development of specific Knowledge, Skills and Abilities (KSAs) that reflect the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…In addition, research has shown that timely feedback makes learning easier, when it is sent back to the students shortly after the assignment is done, and it is most successful (Stevens & Levi, 2013). Similarly, rubrics also allow students to interpret and predict expected levels of output more effectively when presented to students before and during learning (Tractenberg, Attwood, & Via, 2019). According to Andrade as cited by Donlan (2014), rubric promotes thinking and learning and these are beneficial to the students who receive rubric to direct their valuable learning.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research has shown that timely feedback makes learning easier, when it is sent back to the students shortly after the assignment is done, and it is most successful (Stevens & Levi, 2013). Similarly, rubrics also allow students to interpret and predict expected levels of output more effectively when presented to students before and during learning (Tractenberg, Attwood, & Via, 2019). According to Andrade as cited by Donlan (2014), rubric promotes thinking and learning and these are beneficial to the students who receive rubric to direct their valuable learning.…”
Section: Introductionmentioning
confidence: 99%
“…This interactive process enabled instructors to correct misconceptions and provided students with the opportunity to ask clarifying questions. Providing space for dual engagement takes advantage of learning being a social activity, which can facilitate improved content understanding (McClatchy et al, 2020) and motivation for further learning beyond the workshop (Tractenberg et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining five classes have critiques such as a lack of hands-on practice, the use of outdated coding languages and tools, and a lack of application to student research needs. The importance of computational skills training specific to agricultural and natural science researchers is a growing concern (Tractenberg et al, 2019), and it is clear that coursework alone cannot address this gap. Recent recommendations have highlighted the role of stand-alone workshops in meeting student, faculty, and professional training needs (Attwood et al, 2019;McGrath et al, 2019;Tractenberg et al, 2019).…”
Section: The Casementioning
confidence: 99%
“…Learning bioinformatics skills can be incorporated into microbiology courses, at any level. Educators may use the bioinformatics mastery rubric developed by Tractenberg et al (2019) to promote bioinformatics practice in the classroom and lab settings to achieve the associated competencies in undergraduate education. Educators can also choose to include bioinformatics skills in the learning environment using a software carpentry format (https://software-carpentry.…”
Section: A Focus On Bioinformatics Competenciesmentioning
confidence: 99%